STRATEGI PERENCANAAN DAN PENGEMBANGAN OBJEK WISATA (STUDI KASUS PANTAI PANGANDARAN KABUPATEN CIAMIS JAWA BARAT) - Hidayat, Marceilla (THE Journal : Tourism and Hospitality Essentials Journal, 2011)
Tourism can be defined as a whole activity by people who do traveling to stay in one place out of the daily activities for not more than one year for leisure, business, and other purpose. Ecotourism as mentioned on UU No.9 year 1990, article 16 as an objects groups for an attractive tourism can be defined as a unique travel at national park, forest and nature tourism. Bay tourism and marine tourism is a part of Ecotourism. Marine tourism development in general is an effort for developing and using tourism object and marine tourism in Indonesian sea. The consumers behavior patterns from the tourist, they are not focus on leisure enjoying sun, sea and sand but change to higher tourism, that is enjoying the product or cultural creation and heritage. Than nature or ecotourism from one place to other country. This change need to be taken care with a lot of development tourism product also promotion on government and self investor. Marine tourism activities will need a big investment, condition, and law. To handle all this complex problems with optimal, will need to arrange regulation in order using the potential of the sea for tourism activities in marine tourism development. Indonesia so rich with marine assets that can be use or oriented, so that the marine tourism development paradigm must be handle soon with the regulation from all parties, to explore all marine tourism potential through strategic planning with obeying the save principal.